Ambulatory Care of Children Treated with Anticonvulsants – Pitfalls after Discharge from Hospital - Bertsche, A.; Dahse, A.-J.; Neininger, M. P.; Bernhard, M. K.; Syrbe, S.; Frontini, R.; Kiess, W.; Merkenschlager, A.; Bertsche, T. (Klinische Pädiatrie, 2013)
Anticonvulsants require special consideration particularly at the interface from hospital to ambulatory care.Observational study for 6 months with prospectively enrolled consecutive patients in a neuropediatric ward of a university hospital (age 0–<18 years) with long-term therapy of at least one anticonvulsant. Assessment of outpatient prescriptions after discharge. Parent interviews for emergency treatment for acute seizures and safety precautions.We identified changes of the brand in 19/82 (23%) patients caused by hospital’s discharge letters (4/82; 5%) or in ambulatory care (15/82; 18%). In 37/76 (49%) of patients who were deemed to require rescue medication, no recommendation for such a medication was included in the discharge letters. 17/76 (22%) of the respective parents stated that they had no immediate access to rescue medication. Safety precautions were applicable in 44 epilepsy patients. We identified knowledge deficits in 27/44 (61%) of parents.Switching of brands after discharge was frequent. In the discharge letters, rescue medications were insufficiently recommended. Additionally, parents frequently displayed knowledge deficits in risk management.
Keywords: anticonvulsants; ambulatory care; children; adolescents; compliance; generic drugs; risk management